Super-hydrophobic high-thermal-conductivity composite coating as well as preparation method and application thereof
By using a specific composition of superhydrophobic and highly thermally conductive composite coating, the existing coatings have been solved, and the high thermal conductivity and stable superhydrophobic properties are achieved, which are suitable for condensation heat transfer applications in harsh environments.
Patent Information
- Application Number
- CN202411728951.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing superhydrophobic coatings have insufficient thermal conductivity during the fermentation steam condensation process, and have poor alkali corrosion resistance and mechanical stability, making them difficult to effectively apply in harsh environments.
Superhydrophobic and highly thermally conductive composite coating consisting of ethanol solution, dispersant, adhesive agent, dimethyl silicone oil, polytetrafluoroethylene powder, silica, graphene, silicon carbide and hardening and wear-resisting agent are used to form a coating by spraying and staged baking.
It achieves high thermal conductivity, stable superhydrophobic properties, excellent wear resistance and mechanical stability, and is suitable for harsh environments such as acid and alkali, and significantly improves the condensation heat transfer performance.
Smart Images

Figure CN119552543A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coating materials, and in particular relates to a super-hydrophobic high thermal conductivity composite coating and a preparation method and application thereof. Background Art
[0002] A large amount of waste steam will be generated during the aerobic fermentation process of organic solid waste. This waste heat source has the characteristics of low grade (50-70℃) and long production cycle (7-30 days). At present, the most effective and convenient method of fermentation heat recovery is to use an external heat exchanger to capture the heat energy in the fermentation steam. However, fermentation steam is different from industrial waste steam such as boilers. It has a low temperature and is unstable. It belongs to saturated hot and humid air. The presence of non-condensable gas will seriously affect the condensation heat transfer performance. The above problems make the recovery of fermentation waste heat more difficult. The key to optimizing the fermentation waste heat recovery process is to reduce heat loss and improve the heat transfer performance inside the heat exchanger in order to maximize the fermentation heat energy. For heat loss, methods such as optimizing the process and strengthening the insulation of equipment can be used, while for improving the heat transfer performance, the key is to strengthen the condensation heat transfer process of fermentation steam in the heat exchanger.
[0003] For condensation heat transfer inside the heat exchanger, most of the heat and mass transfer is carried out in the form of film condensation. Under the same degree of supercooling, the heat transfer performance during droplet condensation is one order of magnitude higher than that during film condensation. Therefore, promoting the occurrence of droplet condensation can effectively improve the condensation heat transfer performance. By hydrophobic modification of the surface of the heat exchanger, film condensation can be converted into droplet condensation. The common method of hydrophobic modification of the surface of metal heat exchanger is to use hydrophobic polymer materials to attach to the surface of the heat exchanger to form a super-hydrophobic coating with self-cleaning properties. The super-hydrophobic structure enables the water droplets formed by condensation in the heat exchanger to quickly detach from the heat exchange surface, thereby promoting the generation of new water droplets, that is, promoting the process of steam condensation and heat release.
[0004] However, surface modification of metal heat exchanger fins does not significantly improve the condensation heat transfer performance because the thermal conductivity of polymer materials is low, and the thermal conductivity of most metals is 100 times or even 1000 times that of polymers. This results in a significant decrease in the overall thermal conductivity after the coating and the heat exchanger fin substrate are combined, thereby inhibiting the condensation heat transfer performance.
[0005] In addition, the fermentation steam carries a small amount of ammonia and particulate matter, which causes the droplets to have a certain alkalinity after condensation. Therefore, it is necessary to improve the alkali corrosion resistance and chemical stability of the superhydrophobic coating. At the same time, the presence of particulate matter and convective heat transfer will continuously wear the coating. Therefore, the coating still needs to have good wear resistance and mechanical stability.
[0006] At present, there are many methods for preparing super-hydrophobic coatings, but most of them have complicated preparation and modification processes and high costs, making it difficult to achieve mass production and large-scale promotion. Therefore, it is particularly important to develop a low-cost, simple method for preparing high thermal conductivity, super-hydrophobic coatings. Summary of the invention
[0007] In order to solve one or more technical problems existing in the prior art, the present invention aims to provide a super-hydrophobic high thermal conductivity composite coating and its preparation method and application. The super-hydrophobic high thermal conductivity composite coating in the present invention has stable super-hydrophobic properties and excellent thermal conductivity, excellent wear resistance and mechanical stability, is suitable for harsh environments such as acid and alkali, is suitable for places that promote condensation heat transfer enhancement, and is particularly suitable for heat exchange places such as vapor-liquid / gas heat exchangers.
[0008] The present invention provides a super-hydrophobic high thermal conductivity composite coating in a first aspect, wherein the super-hydrophobic high thermal conductivity composite coating is formed by a super-hydrophobic high thermal conductivity composite coating, and the super-hydrophobic high thermal conductivity composite coating comprises the following components in parts by mass: 60 to 80 parts of ethanol solution, 3 to 5 parts of dispersant, 3 to 5 parts of adhesion agent, 0.3 to 0.5 parts of dimethyl silicone oil, 8 to 10 parts of polytetrafluoroethylene powder, 1 to 2 parts of silicon dioxide, 0.8 to 1.2 parts of graphene, 2 to 3 parts of silicon carbide, 1.2 to 1.5 parts of hardening and wear-resistant agent and 4 to 6 parts of polytetrafluoroethylene emulsion.
[0009] Preferably, the ethanol solution is an ethanol aqueous solution, the volume percentage of ethanol in the ethanol aqueous solution is 80-90%; and / or the solid content of the polytetrafluoroethylene emulsion is 40%-60%.
[0010] Preferably, the dispersant is a sodium salt of polycarboxylate dispersant; the adhesion agent is a modified silane polymer; the silica is silica modified by silane coupling agent KH-550; the graphene is a few-layer graphene or a single-layer graphene, and preferably, the carbon content in the graphene is not less than 98wt%; and / or the hardening and wear-resistant agent is a modified organosilicon complex nano-silicon solution.
[0011] Preferably, the particle size of the polytetrafluoroethylene powder does not exceed 1 μm; the particle size of the silicon dioxide does not exceed 20 nm; the particle size D50 of the graphene does not exceed 12 μm; and / or the particle size of the silicon carbide does not exceed 1 μm.
[0012] In a second aspect, the present invention provides a method for preparing the super-hydrophobic high thermal conductive composite coating according to the first aspect of the present invention, the method comprising the following steps:
[0013] (1) adding a dispersant, an adhesive and dimethyl silicone oil to an ethanol solution and stirring the mixture to obtain a solution A;
[0014] (2) adding polytetrafluoroethylene powder, silicon dioxide, graphene and silicon carbide to solution A and uniformly dispersing them by ultrasonication to obtain solution B;
[0015] (3) adding a hardening and anti-wear agent and polytetrafluoroethylene emulsion to solution B and uniformly dispersing by ultrasonication, and then filtering through a sieve with a mesh size of 100 or more to obtain a super-hydrophobic and high thermal conductive composite coating;
[0016] (4) The substrate is pretreated, and then the super-hydrophobic high thermal conductive composite coating is sprayed on the substrate, and then baked to obtain a super-hydrophobic high thermal conductive composite coating on the substrate.
[0017] Preferably, in step (2) and / or step (3), the ultrasonic dispersion time is 15 to 30 minutes, preferably 20 minutes.
[0018] Preferably, the spraying is performed under a pressure of 0.2-0.4 MPa, and the distance between the spray gun used during the spraying and the substrate is 100-250 mm.
[0019] Preferably, the baking is firstly baking at 250-280° C. for 10-20 min, and then baking at 360-400° C. for 10-30 min; and / or the heating rate to the baking temperature is 5-10° C. / min.
[0020] In a third aspect, the present invention provides a super-hydrophobic and high thermal conductive composite coating prepared by the preparation method described in the second aspect of the present invention; preferably, the water contact angle of the super-hydrophobic and high thermal conductive composite coating is above 159°, the thermal conductivity is 18.4W / (m·K), the adhesion is level 0 or level 1, and the pencil hardness is above 3H; preferably, the water contact angle of the super-hydrophobic and high thermal conductive composite coating after wear and peeling test is above 157°, and the water contact angle after acid-base corrosion test in the pH range of 3 to 11 for 24 hours is above 154°.
[0021] In a fourth aspect, the present invention provides an application of the super-hydrophobic and high-thermal-conductivity composite coating described in the first aspect of the present invention or the super-hydrophobic and high-thermal-conductivity composite coating prepared by the preparation method described in the second aspect of the present invention in enhancing condensation heat transfer.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) The super-hydrophobicity of the super-hydrophobic high thermal conductivity composite coating of the present invention is mainly provided by the combined action of the four components of silicon dioxide, graphene, dimethyl silicone oil and polytetrafluoroethylene, which constructs a surface structure with high roughness and low surface energy. The present invention finds that the surface structure with high roughness and low surface energy is also conducive to improving the super-hydrophobicity of the coating; the high thermal conductivity of the super-hydrophobic high thermal conductivity composite coating of the present invention is mainly provided by the combined action of the three components of graphene, silicon carbide and silicon dioxide, and three solid fillers of different dimensions are evenly dispersed in the coating to form an interlaced thermal conductive network, which is conducive to improving the thermal conductivity of the coating; the excellent wear resistance and bonding strength of the super-hydrophobic high thermal conductivity composite coating of the present invention are mainly strengthened by the adhesion agent, silicon carbide and hardening and wear-resistant agent, especially the synergistic action of the adhesion agent and the hardening and wear-resistant agent, and the inorganic filler, the metal substrate and the organic resin (polytetrafluoroethylene component) are connected by cross-linking, which effectively improves the adhesion and / or hardness of the coating.
[0024] (2) When preparing the super-hydrophobic high thermal conductivity composite coating of the present invention, the super-hydrophobic high thermal conductivity composite coating can be first obtained by a blending method, and then the super-hydrophobic high thermal conductivity composite coating is formed by a spraying + baking method. The water contact angle of the super-hydrophobic high thermal conductivity composite coating of the present invention reaches 159° or more, and the rolling angle is less than 4°. After the coating is coated on a 2.5 mm thick stainless steel plate, the overall thermal conductivity can preferably reach 18.4 W / (m·K) or more, which is higher than the stainless steel substrate; and the super-hydrophobic high thermal conductivity composite coating of the present invention has excellent adhesion (GB / T9286-1998 standard, grade 0 or 1) and hardness (pencil hardness 3H or more); after wear and peeling tests, the water contact angle thereof does not change much (the water contact angle can still be maintained at more than 157°), and after a one-day acid-base corrosion test, it still has super-hydrophobicity (the water contact angle can still be maintained at more than 154°) in the pH range of 3 to 11.
[0025] (3) The raw materials used in the super-hydrophobic high thermal conductivity composite coating and super-hydrophobic high thermal conductivity composite coating of the present invention are low in cost and can be purchased on the market. The raw material cost of the finished coating prepared on a small scale in the laboratory is not more than 265 yuan / kg. The preparation process of the super-hydrophobic high thermal conductivity coating of the present invention is simple to operate, and is a simple blending method. The coating can be prepared by a spraying + baking method without the need for specific instruments and equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is an AFM image of the super-hydrophobic and high thermal conductive composite coating obtained in Example 1 of the present invention;
[0027] Figure 2 is an AFM image of the coating obtained in Comparative Example 1 of the present invention;
[0028] Figure 3is a performance test result curve diagram of the super-hydrophobic high thermal conductive composite coating obtained in Example 1 of the present invention; Figure 3 In the figure, (a) corresponds to the wear test result curve; (b) corresponds to the peeling test result curve; (c) corresponds to the water impact test result curve; (d) corresponds to the acid-base corrosion test result curve. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In a first aspect, the present invention provides a super-hydrophobic high thermal conductivity composite coating, wherein the super-hydrophobic high thermal conductivity composite coating is formed by a super-hydrophobic high thermal conductivity composite coating, and the super-hydrophobic high thermal conductivity composite coating comprises the following components in parts by mass:
[0031] 60-80 parts (e.g. 60, 65, 70, 75 or 80 parts) of ethanol solution, 3-5 parts (e.g. 3, 3.5, 4, 4.5 or 5 parts) of dispersant, 3-5 parts (e.g. 3, 3.5, 4, 4.5 or 5 parts) of adhesive, 0.3-0.5 parts (e.g. 0.3, 0.4 or 0.5 parts) of dimethyl silicone oil, 8-10 parts (e.g. 8, 9 or 10 parts) of polytetrafluoroethylene powder, 1-2 parts (e.g. 10 parts) of silicon dioxide For example, 1, 1.2, 1.5, 1.8 or 2 parts), graphene 0.8-1.2 parts (for example, 0.8, 0.9, 1, 1.1 or 1.2 parts), silicon carbide 2-3 parts (for example, 2, 2.2, 2.5, 2.8 or 3 parts), hardening and wear-resistant agent 1.2-1.5 parts (for example, 1.2, 1.3, 1.4 or 1.5 parts) and polytetrafluoroethylene emulsion 4-6 parts (for example, 4, 4.5, 5, 5.5 or 6 parts); in this In the invention, "parts" all refer to "parts by mass". In specific embodiments and comparative examples, the units of parts by mass can be unified as weight units such as "g" or "kg"; in the present invention, for example, a super-hydrophobic and high-thermal-conductivity composite coating can be prepared by spraying and then baking, and a super-hydrophobic and high-thermal-conductivity composite coating can be quickly constructed; the baking is first baked at 250-280°C (for example, 250°C, 260°C, 270°C or 280°C) for 10-20min (for example, 10, 15 or 20min), and then baked at 360-400°C (for example, 360°C, 370°C, 380°C, 390°C or 400°C) for 10-30min (for example, 10, 15, 20, 25 or 30min); the heating rate for heating to the baking temperature is 5-10°C / min (for example, 5, 6, 7, 8 or 9°C / min).
[0032] The present invention finds that after the super-hydrophobic high thermal conductivity composite coating is sprayed, the baking method of staged (baking 10-20min+360-400°C at 250-280°C for 10-30min) can be used to effectively improve the performance of the super-hydrophobic high thermal conductivity composite coating formed, because the staged baking used by the present invention helps to gradually remove the solvent and moisture in the coating, reduce the formation of bubbles or pores, and can promote the uniform curing of the coating and the discharge of bubbles, so as to form a more dense coating structure, which helps to improve the super-hydrophobic performance and hardness of the surface. In addition, baking at low temperature stage, the coating can be better combined with the substrate surface, and then baking at high temperature stage for cross-linking or curing, and the adhesion of the coating can be enhanced. The super-hydrophobicity of the super-hydrophobic high thermal conductivity composite coating in the present invention is mainly provided by the joint action of the four components of silicon dioxide, graphene, dimethyl silicone oil and polytetrafluoroethylene, but it is also inseparable from the high roughness and low surface energy surface structure constructed by the other components. The present invention finds that the surface structure with high roughness and low surface energy is also conducive to improving the super-hydrophobic performance of the coating; the high thermal conductivity of the super-hydrophobic high thermal conductivity composite coating in the present invention is mainly provided by the joint action of the three components of graphene, silicon carbide and silicon dioxide, and three solid fillers of different dimensions are in the coating. Uniform dispersion forms an interlaced heat-conducting network, which is beneficial to improving the thermal conductivity of the coating, but it is also inseparable from the influence of other components on the formed heat-conducting network structure; the excellent wear resistance and bonding strength of the super-hydrophobic high thermal conductivity composite coating of the present invention are mainly strengthened by the adhesion agent, silicon carbide and hardening wear-resistant agent, especially the synergistic effect of the adhesion agent and the hardening wear-resistant agent, and the inorganic filler, the metal substrate and the organic resin (polytetrafluoroethylene component) are connected by cross-linking, which effectively improves the adhesion and / or hardness of the coating, but the other components will also affect the cross-linking effect. The present invention finds that the components contained in the super-hydrophobic high thermal conductive composite coating need to control the appropriate content. If the content of each component is inappropriate, it will have an adverse effect on the super-hydrophobicity, thermal conductivity, wear resistance, mechanical stability and / or adhesion of the coating. For example, excessive hardening and wear resistance will significantly affect the hydrophobicity of the coating. If the amount of dimethyl silicone oil is too much, the hardness and adhesion of the coating will be significantly reduced. For example, excessive graphene or silicon carbide powder will also increase the porosity of the coating, affecting the density, thereby affecting the overall performance of the coating.
[0033] The super-hydrophobic and high-thermal-conductivity composite coating of the present invention has stable super-hydrophobic properties and excellent thermal conductivity, excellent wear resistance and mechanical stability, is suitable for harsh environments such as acid and alkali, is suitable for places that promote condensation heat transfer enhancement, and is especially suitable for heat exchange places such as steam-liquid / gas heat exchangers; the super-hydrophobic and high-thermal-conductivity composite coating of the present invention can be used as a super-hydrophobic and high-thermal-conductivity durable coating (super-hydrophobic and high-thermal-conductivity composite coating) for enhancing condensation heat transfer.
[0034] According to some preferred embodiments, the ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 80-90% (for example, 80%, 85% or 90%). In the present invention, the ethanol aqueous solution contains some water, which can hydrolyze the adhesion agent; and / or the solid content of the polytetrafluoroethylene emulsion is 40%-60%. The present invention does not make any specific limitation on the polytetrafluoroethylene emulsion, and commercially available products can be used.
[0035] According to some preferred embodiments, the dispersant is a polycarboxylate sodium salt dispersant; the present invention does not specifically limit the polycarboxylate sodium salt dispersant, for example, a product that can be directly purchased can be used; in some specific embodiments, the polycarboxylate sodium salt dispersant is, for example, a polycarboxylate sodium salt dispersant SN-DISPERSANT 5040; the adhesive is a modified silane polymer; in the present invention, the adhesive is an adhesion promoter, and the main component is a modified silane polymer; in some specific embodiments, the adhesive can be, for example, an adhesive SRE-6015W, the main component of which is a modified silane polymer; the silica is silica modified by a silane coupling agent KH-550, and the present invention uses silica modified by a silane coupling agent KH-550 to improve the hydrophobicity of the coating, while if unmodified silica is used, it will affect the hydrophobicity of the coating; the present invention The silica modified by the silane coupling agent KH-550 is not specifically limited, and the directly purchased product or the silica modified by the silane coupling agent KH-550 obtained by the existing method can be used; in some specific embodiments, the silica is, for example, silica modified by the silane coupling agent KH-550 and having a model of ZD-SiO2-Z22. The silica of model ZD-SiO2-Z22 can be purchased from Jinan Zhiding Welding Material Co., Ltd., and the particle size is preferably 20 nm, and the specific surface area is preferably 230 m 2 / g; the graphene is a few-layer graphene or a single-layer graphene, preferably, the graphene is a single-layer graphene, preferably, the carbon content in the graphene is not less than 98wt%; and / or the hardening and wear-resistant agent is a modified organic silicon complex nano-silicon solution; the present invention has no special requirements for the hardening and wear-resistant agent, and commercially available products can be used. In the present invention, preferably, the hardening and wear-resistant agent is the hardening and wear-resistant agent SRE-5250. In the present invention, the mass percentage of silicon dioxide (SiO2) in the hardening and wear-resistant agent SRE-5250 is 35%.
[0036] According to some preferred embodiments, the particle size of the polytetrafluoroethylene powder does not exceed 1 μm; the particle size of the silicon dioxide does not exceed 20 nm; the particle size D50 of the graphene does not exceed 12 μm; and / or the particle size of the silicon carbide does not exceed 1 μm.
[0037] In a second aspect, the present invention provides a method for preparing the super-hydrophobic high thermal conductive composite coating according to the first aspect of the present invention, the method comprising the following steps:
[0038] (1) adding a dispersant, an adhesive and dimethyl silicone oil to an ethanol solution and stirring the mixture to obtain a solution A;
[0039] (2) adding polytetrafluoroethylene powder, silicon dioxide, graphene and silicon carbide to solution A and uniformly dispersing them by ultrasonication to obtain solution B;
[0040] (3) adding a hardening and anti-wear agent and polytetrafluoroethylene emulsion to solution B and uniformly dispersing by ultrasonication, and then filtering through a sieve with a mesh size of 100 or more to obtain a super-hydrophobic and high thermal conductivity composite coating; in the present invention, the sieve is, for example, a stainless steel sieve;
[0041] (4) Pre-treating the substrate, spraying the super-hydrophobic high thermal conductivity composite coating on the substrate, and then baking to obtain a super-hydrophobic high thermal conductivity composite coating on the substrate; in the present invention, the substrate is, for example, a stainless steel and / or copper substrate; the pre-treatment is, for example, cleaning, drying and pre-heating the substrate; in the present invention, the pre-heating is, for example, preheating at 80 to 100° C. for 5 to 10 minutes.
[0042] When preparing the super-hydrophobic high thermal conductivity composite coating of the present invention, a super-hydrophobic high thermal conductivity composite coating can be first obtained by a blending method, and then the super-hydrophobic high thermal conductivity composite coating is formed by a spraying + baking method. The water contact angle of the super-hydrophobic high thermal conductivity composite coating of the present invention reaches 159° or more, and the rolling angle is less than 4°. After the coating is applied on a 2.5 mm thick stainless steel plate, the overall thermal conductivity can reach 18.4W / (m·K) or more, which is higher than the stainless steel substrate; and the super-hydrophobic high thermal conductivity composite coating of the present invention has excellent adhesion (adhesion) (GB / T9286-1998 standard, grade 0 or 1) and hardness (pencil hardness 3H or more); after wear and peeling tests, the water contact angle thereof does not change much (the water contact angle can still be maintained at more than 157°), and after an acid-base corrosion test lasting 1 day, it still has super-hydrophobicity (the water contact angle can still be maintained at more than 154°) in the pH range of 3 to 11. The raw materials used in the super-hydrophobic high thermal conductivity composite coating and the super-hydrophobic high thermal conductivity composite coating of the present invention are low in cost and can be purchased on the market. The raw material cost of the finished coating prepared on a small scale in the laboratory is not more than 265 yuan / kg. The preparation process of the super-hydrophobic high thermal conductivity coating of the present invention is simple to operate, and is a simple blending method. The coating can be prepared by a spraying + baking method without the need for specific instruments and equipment.
[0043] According to some preferred embodiments, in step (2) and / or step (3), the ultrasonic dispersion time is 15 to 30 min (e.g., 15, 20, 25 or 30 min), preferably 20 min; in the present invention, the ultrasonic dispersion is performed, for example, using an ultrasonic cleaner.
[0044] According to some preferred embodiments, the spraying is carried out under a pressure (air pressure) of 0.2 to 0.4 MPa (for example, 0.2, 0.3 or 0.4 MPa), and the distance between the spray gun used during spraying and the substrate is 100 to 250 mm (for example, 100, 120, 150, 180, 200, 220 or 250 mm); in the present invention, it is preferred to spray at an air pressure of 0.2 to 0.4 MPa, which can ensure that the coating is evenly distributed and effectively covers the surface of the substrate, helping to form a uniform coating and avoid sagging or omissions, and a higher air pressure can better atomize the coating, making the particles smaller, thereby improving the adhesion of the coating, and can improve the spraying efficiency, reduce the waste of coating, and save material costs.
[0045] According to some preferred embodiments, the baking is firstly baked at 250-280°C (e.g., 250°C, 260°C, 270°C or 280°C) for 10-20min (e.g., 10, 15 or 20min), and then baked at 360-400°C (e.g., 360°C, 370°C, 380°C, 390°C or 400°C) for 10-30min (e.g., 10, 15, 20, 25 or 30min); and / or the heating rate to the baking temperature is 5-10°C / min (e.g., 5, 6, 7, 8 or 9°C / m in); The present invention finds that after the super-hydrophobic high thermal conductivity composite coating is sprayed, the baking method of adopting staged (baking 10-20min+360-400℃ baking 10-30min at 250-280℃), the performance of the super-hydrophobic high thermal conductivity composite coating formed can be effectively improved, this is because the staged baking adopted by the present invention helps to gradually remove the solvent and moisture in the coating, reduces the formation of bubbles or pores, can promote the uniform curing of the coating and the discharge of bubbles, so as to form a more dense coating structure, help to improve the super-hydrophobic performance and hardness of the surface, etc. In addition, baking at low temperature stage, the coating can be better combined with the substrate surface, and then baking at high temperature stage for cross-linking or curing, and the adhesion of the coating can be enhanced.
[0046] According to some specific embodiments, the super hydrophobic high thermal conductive composite coating is prepared as follows:
[0047] ① In 60 to 80 parts of ethanol aqueous solution with a volume percentage of 80% to 90% ethanol, add 3 to 5 parts of dispersant (polycarboxylic acid sodium salt dispersant SN-DISPERSANT 5040), 3 to 5 parts of adhesive (adhesive SRE-6015W) and 0.3 to 0.5 parts of dimethyl silicone oil (dimethyl silicone oil PMX-200), stir evenly, and obtain solution A.
[0048] ② In the solution A obtained in step ①, add 8 to 10 parts of polytetrafluoroethylene powder, 1 to 2 parts of silicon dioxide, 0.8 to 1.2 parts of graphene and 2 to 3 parts of silicon carbide four fillers, and then disperse them in an ultrasonic cleaner for 20 minutes to obtain solution B; wherein the particle size of the polytetrafluoroethylene powder is preferably not more than 1 μm; the silicon dioxide is silicon dioxide modified by silane coupling agent KH-550 and model ZD-SiO2-Z22, and the particle size is preferably not more than 20 nm; the graphene is a few-layer graphene or a single-layer graphene, preferably a single-layer graphene, the carbon content of the single-layer graphene is not less than 98%, and the particle size D50 is preferably not more than 12 μm; the particle size of the silicon carbide is preferably not more than 1 μm.
[0049] ③ In the solution B obtained in step ②, 1.2 to 1.5 parts of a hardening and wear-resistant agent (hardening and wear-resistant agent SRE-5250, containing 35 wt% of SiO2 as an effective ingredient) and 5 parts of polytetrafluoroethylene emulsion are added while stirring, and then dispersed for 20 minutes through an ultrasonic cleaner, and filtered through a stainless steel mesh of more than 100 meshes to obtain a super-hydrophobic and high-thermal conductive composite coating; wherein the solid content of the polytetrafluoroethylene emulsion is 40% to 60%.
[0050] ④ After the stainless steel plate and / or copper plate substrate is polished, cleaned, dried and preheated, spray the stainless steel plate and / or copper plate substrate with a spray gun at a distance of 100 to 250 mm from the stainless steel plate and / or copper plate substrate, perpendicular to the plate surface, under an air pressure of 0.2 to 0.4 MPa; then bake and shape in an oven, and set the heating rate to 5 to 10 ° C / min: first increase the temperature to 260 ° C at a heating rate of 5 to 10 ° C / min, and bake at a constant temperature for 10 to 20 minutes, then increase the temperature to 380 ° C at a heating rate of 5 to 10 ° C / min, bake at a constant temperature for 10 to 30 minutes, and finally cool naturally to room temperature, so as to obtain a super hydrophobic and high thermal conductivity composite coating on the substrate.
[0051] The present invention provides, in a third aspect, a super-hydrophobic and high-thermal-conductivity composite coating prepared by the preparation method described in the second aspect of the present invention.
[0052] According to some preferred embodiments, the water contact angle of the super hydrophobic and high thermal conductive composite coating is above 159°, the thermal conductivity is 18.4W / (m·K), the adhesion is level 0 or level 1, and the pencil hardness is above 3H; preferably, the water contact angle of the super hydrophobic and high thermal conductive composite coating after wear and peeling test is above 157°, and the water contact angle after acid-base corrosion test with a pH range of 3 to 11 for 24 hours is above 154°.
[0053] In a fourth aspect, the present invention provides an application of the super-hydrophobic and high-thermal-conductivity composite coating described in the first aspect of the present invention or the super-hydrophobic and high-thermal-conductivity composite coating prepared by the preparation method described in the second aspect of the present invention in enhancing condensation heat transfer.
[0054] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0055] Example 1
[0056] ① In 70 parts of ethanol solution with a volume percentage of 85% ethanol, add 3 parts of dispersant (polycarboxylate sodium salt dispersant SN-DISPERSANT 5040), 5 parts of adhesive (adhesive SRE-6015W) and 0.5 parts of dimethyl silicone oil (dimethyl silicone oil PMX-200), stir evenly to obtain solution A.
[0057] ② In the solution A obtained in step ①, four fillers, namely, 10 parts of polytetrafluoroethylene powder, 1.5 parts of silicon dioxide, 1.2 parts of graphene and 3 parts of silicon carbide, are added, and then dispersed in an ultrasonic cleaner for 20 minutes to obtain a solution B; wherein the particle size of the polytetrafluoroethylene powder is 1 μm; the silicon dioxide is silicon dioxide modified by a silane coupling agent KH-550, model ZD-SiO2-Z22, and has a particle size of 20 nm; the graphene is a single-layer graphene, the carbon content of the single-layer graphene is 98wt%, and the particle size D50 is 12 μm; the particle size of the silicon carbide is 1 μm.
[0058] ③ In the solution B obtained in step ②, 1.5 parts of hardening and wear-resistant agent (hardening and wear-resistant agent SRE-5250, containing 35wt% of SiO2 as an effective ingredient) and 5 parts of polytetrafluoroethylene emulsion were added while stirring, and then dispersed for 20 minutes through an ultrasonic cleaner, and filtered through a 100-mesh stainless steel mesh to obtain a super-hydrophobic and high-thermal conductive composite coating; wherein the solid content of the polytetrafluoroethylene emulsion is 60%.
[0059] ④ Use a 0.4 mm thick stainless steel plate as a substrate, grind, clean, dry and preheat the stainless steel plate, and then use a spray gun to spray the super hydrophobic and high thermal conductive composite coating obtained in step ③ at a distance of 180 mm from the stainless steel plate substrate, perpendicular to the plate surface under an air pressure of 0.3 MPa; then bake and shape in an oven, and set the heating rate to 5 ° C / min: first increase the temperature to 260 ° C at a heating rate of 5 ° C / min, and bake at a constant temperature for 15 minutes, then increase the temperature to 380 ° C at a heating rate of 5 ° C / min, bake at a constant temperature for 25 minutes, and finally cool naturally to room temperature, that is, obtain a super hydrophobic and high thermal conductive composite coating on the substrate.
[0060] Embodiments 2 to 19
[0061] Examples 2 to 19 are substantially the same as Example 1, except that some components in the adopted formula are different from those in Example 1. The specific differences are shown in Table 1 below.
[0062] Table 1
[0063]
[0064]
[0065] Comparative Example 1
[0066] This comparative example provides a commercial polytetrafluoroethylene emulsion as a coating, and a coating is formed by the same method as step ④ in Example 1; wherein the solid content of the polytetrafluoroethylene emulsion is 60%.
[0067] Comparative Example 2
[0068] Comparative Example 2 is substantially the same as Example 1, except that:
[0069] ④ A stainless steel plate with a thickness of 0.4 mm is used as a substrate. After the stainless steel plate is polished, cleaned, dried and preheated, the super-hydrophobic and high-thermal-conductive composite coating obtained in step ③ is sprayed perpendicular to the plate surface at a position 180 mm away from the base of the stainless steel plate with a spray gun under an air pressure of 0.3 MPa; then it is baked and formed in an oven, the heating rate is set to 5°C / min, the temperature is increased to 260°C at a heating rate of 5°C / min, and the constant temperature baking is performed for 40 minutes, and finally naturally cooled to room temperature to obtain a composite coating on the substrate.
[0070] Comparative Example 3
[0071] Comparative Example 3 is substantially the same as Example 1, except that:
[0072] ④ A stainless steel plate with a thickness of 0.4 mm is used as a substrate. After the stainless steel plate is polished, cleaned, dried and preheated, the super-hydrophobic and high-thermal-conductive composite coating obtained in step ③ is sprayed perpendicular to the plate surface at a position 180 mm away from the base of the stainless steel plate with a spray gun under an air pressure of 0.3 MPa; then it is baked and formed in an oven, the heating rate is set to 5°C / min, the temperature is increased to 380°C at a heating rate of 5°C / min, and constant temperature baking is performed for 40 minutes, and finally naturally cooled to room temperature to obtain a composite coating on the substrate.
[0073] The present invention performs performance tests on the coatings finally obtained in each embodiment and each ratio, and the test results are shown in Table 2; wherein the water contact angle is the average value of 3 to 5 measurements; the thermal conductivity is the thermal conductivity of the coating formed by spraying the coating in each embodiment or each comparative example on a 2.5 mm thick stainless steel plate using the same method as step ④ in embodiment 1 measured by a laser thermal conductivity meter; the pencil hardness is measured according to GB / T 6739-2022 standard; and the adhesion grade is measured according to GB / T9286-1998 standard.
[0074] Table 2
[0075]
[0076]
[0077] The present invention performs AFM characterization on the super hydrophobic high thermal conductive composite coating obtained in Example 1 and the coating obtained in Comparative Example 1. The AFM results are as follows: Figure 1 and Figure 2 As shown; the AFM characterization results show that the roughness Ra of the coating in Comparative Example 1 is 55 nm, and the roughness Ra of the super-hydrophobic and high thermal conductive composite coating in Example 1 is 119.6 nm; this indicates that the super-hydrophobic and high thermal conductive composite coating in the present invention has excellent super-hydrophobicity after doping, which also benefits from its own higher roughness after doping.
[0078] The present invention also conducts mechanical stability and chemical stability tests on the super hydrophobic high thermal conductivity composite coating in Example 1, and the test method is as follows:
[0079] 1. Wear test: Place 800-grit sandpaper face down on the coated sample, then place a 150g weight on the overlapping part of the sandpaper and the sample to make the sample test area and the sandpaper in close contact. Move the sample back and forth 10cm in a specific direction, then rotate 90° and move the same distance; this process represents a wear cycle, and the change in the water contact angle of the sample is recorded every 20 cycles. The wear test result curve is as follows: Figure 3 (a) shown.
[0080] 2. Peeling test: The coated sample was peeled off with a strong tape (3M 600-1PK model, with an adhesive force of (10±1)N / 25mm), and a 1.0 kg weight was placed to ensure complete adhesion of the tape. The change in the water contact angle of the sample was recorded after every 30 peeling cycles. The peeling test result curve was as follows: Figure 3 (b) as shown.
[0081] 3. Water impact test: The coating sample is fixed on a 45° inclined surface, and water drops are continuously dropped from a height of 50 cm at a speed of 20 mL / min. The wettability (water contact angle) of the sample is recorded once every 30 minutes. The water impact test result curve is as follows: Figure 3 (c) as shown.
[0082] 4. Chemical stability test: Use HCl solution / NaOH solution with pH=1-13 to corrode the coating surface for 24 hours, test the water contact angle of the coating after corrosion, and measure the acid-base corrosion test result curve as shown below: Figure 3 (d) shows that the result corresponding to pH=7 is the result obtained by corroding the coating surface with a 3.5wt% NaCl aqueous solution for 24h.
[0083] from Figure 3 The results show that after the stability test, the contact angle of the coating can be maintained above 151.5°; among them, its mechanical stability is even better. After wear and peeling tests, its water contact angle does not change much (the water contact angle can still be maintained above 157°); the water impact resistance of the coating is relatively poor, but the super-hydrophobic structure can still be maintained during the test; in the alkali corrosion resistance test, after 1 day (24h) of acid and alkali corrosion test, in the pH range of 3-11, it still has super-hydrophobicity (the water contact angle can still be maintained above 154°), but because the coating is doped with silica, graphene and other substances, the density of the coating is slightly reduced, and the surface hydrophobic structure may be destroyed after long-term strong alkali corrosion (pH not less than 13, corrosion time greater than 24h).
[0084] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A super hydrophobic high thermal conductive composite coating, characterized in that: The super-hydrophobic high thermal conductivity composite coating is formed by a super-hydrophobic high thermal conductivity composite coating, and the super-hydrophobic high thermal conductivity composite coating comprises the following components in parts by mass: 60-80 parts of ethanol solution, 3-5 parts of dispersant, 3-5 parts of adhesion agent, 0.3-0.5 parts of dimethyl silicone oil, 8-10 parts of polytetrafluoroethylene powder, 1-2 parts of silicon dioxide, 0.8-1.2 parts of graphene, 2-3 parts of silicon carbide, 1.2-1.5 parts of hardening and wear-resistant agent and 4-6 parts of polytetrafluoroethylene emulsion.
2. The super-hydrophobic high thermal conductive composite coating according to claim 1, characterized in that: The ethanol solution is an ethanol aqueous solution, and the volume percentage of ethanol in the ethanol aqueous solution is 80-90%; and / or The solid content of the polytetrafluoroethylene emulsion is 40% to 60%.
3. The super hydrophobic high thermal conductive composite coating according to claim 1, characterized in that: The dispersant is a polycarboxylate sodium salt dispersant; The adhesive is a modified silane polymer; The silicon dioxide is silicon dioxide modified by silane coupling agent KH-550; The graphene is a few-layer graphene or a single-layer graphene, and preferably, the carbon content in the graphene is not less than 98wt%; and / or The hardening and wear-resistant agent is a modified organic silicon complex nano silicon solution.
4. The super-hydrophobic high thermal conductive composite coating according to claim 1, characterized in that: The particle size of the polytetrafluoroethylene powder does not exceed 1 μm; The particle size of the silicon dioxide does not exceed 20 nm; The particle size D50 of the graphene is no more than 12 μm; and / or The particle size of the silicon carbide is no more than 1 μm.
5. The method for preparing a super-hydrophobic high thermal conductive composite coating according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) adding a dispersant, an adhesive and dimethyl silicone oil to an ethanol solution and stirring the mixture to obtain a solution A; (2) adding polytetrafluoroethylene powder, silicon dioxide, graphene and silicon carbide to solution A and uniformly dispersing them by ultrasonication to obtain solution B; (3) adding a hardening and anti-wear agent and polytetrafluoroethylene emulsion to solution B and uniformly dispersing by ultrasonication, and then filtering through a sieve with a mesh size of 100 or more to obtain a super-hydrophobic and high thermal conductive composite coating; (4) The substrate is pretreated, and then the super-hydrophobic high thermal conductive composite coating is sprayed on the substrate, and then baked to obtain a super-hydrophobic high thermal conductive composite coating on the substrate.
6. The preparation method according to claim 5, characterized in that: In step (2) and / or step (3), the ultrasonic dispersion time is 15 to 30 minutes, preferably 20 minutes.
7. The preparation method according to claim 5, characterized in that: The spraying is carried out under the condition of a pressure of 0.2-0.4 MPa, and the distance between the spray gun used during the spraying and the substrate is 100-250 mm.
8. The preparation method according to claim 5, characterized in that: The baking is firstly baking at 250-280°C for 10-20min, and then baking at 360-400°C for 10-30min; and / or The heating rate to the baking temperature is 5 to 10°C / min.
9. A super-hydrophobic and high thermal conductive composite coating prepared by the preparation method according to any one of claims 5 to 8; Preferably, the water contact angle of the super-hydrophobic high thermal conductive composite coating is above 159°, the thermal conductivity is 18.4W / (m·K), the adhesion is level 0 or level 1, and the pencil hardness is above 3H; Preferably, the water contact angle of the super hydrophobic and high thermal conductive composite coating after wear and peeling tests is above 157°, and the water contact angle after 24 hours of acid-base corrosion test in the pH range of 3 to 11 is above 154°.
10. Use of the super-hydrophobic and high-thermal-conductivity composite coating according to any one of claims 1 to 4 or the super-hydrophobic and high-thermal-conductivity composite coating prepared by the preparation method according to any one of claims 5 to 8 in enhancing condensation heat transfer.
Citation Information
Patent Citations
Preparation method of SiO2 / polytetrafluoroethylene hybridized super-hydrophobic coating
CN103964701A
Method for preparing super hydrophobic polymer composite coating containing nano particles and product thereof
CN103992701A
High-temperature resistant heat-conduction self-cleaning coating and preparation method thereof
CN109554110A
Method for converting traditional paint into superhydrophobic paint
CN109777260A
Hydrophobic powder / polytetrafluoroethylene composite material and preparation method thereof
CN113308075A